Assessment of Human Factors & Ergonomics effecting Patient Safety Culture in a Tertiary Healthcare setting of a South Asian country - Rajesh Harsvardhan; Ayush Mehrotra; Amit Agarwal; Pulak Sharma; Gaurav Pandey; Anu Behari (Patient Safety and Quality Improvement Journal)
Introduction: The Patient Safety (PS) movement dates back to the 1950s, but in recent decades has caught up in swift momentum and is also influencing the Indian healthcare scenario - a lot of work has been done on the global scenario and we are just catching up. Materials & Methodology: This baseline study assesses the current status of Human Factors & Ergonomics w.r.t. Patient Safety Culture in a tertiary healthcare institution of Northern India within a study population of Doctors (Faculty & Resident), Nursing Staff (Graduates & Undergraduates), and Technicians - a first of its kind for the region. The overall response rate was obtained on the (customized & validated) Hospital Survey on Patient Safety Culture (HSOPSC) toolkit.Result: The overall response rate came to 75.7% and the composite Patient Safety Culture score was 46.35% (with internal variations).Conclusion: This calls for introspection to lift the overall standards of PS and PSC and to build further upon them.